Pelatihan Perhitungan Harga Pokok Produksi dan Harga Jual berbasis Digital serta Rencana Bisnis untuk Peningkatan Tata Kelola UMKM pada UMKM Koperasi Produsen Sinergy Maju Makmur Medan - Nurlinda; Purwa Hasan Putra; Vivianti Novita (Politeknik Piksi Ganesha Indonesia, 2024)
This activity aims to assist MSME partners of the Koperasi Produsen Sinergy Maju Makmur Medan. PKM was carried out in Mei 2024 by the implementing team, namely 3 Medan Politeknik Negeri Medan lecturers and students together with Partners which was attended by 20 UMKM and 20 Students. The material presented in this PKM activity is the calculation of the cost price and selling price of the product, as well as the preparation of business planning documents. The results of this service activity increase the experience and knowledge of MSMEs regarding the importance of cost price calculations and thorough business planning documents.